To swoon and to spar : a novel - Waters, Martha, 1988- (Waters, Martha, 1988- Regency vows series, 2023)
"The Regency Vows series that is 'sure to delight Bridgerton fans' (USA TODAY) returns with this story about a viscount and his irascible new wife who hopes to chase her husband from their shared home so that she can finally get some peace and quiet--only to find that his company is not as onerous as she thought. Viscount Penvale has been working for years to buy back his ancestral home, Trethwick Abbey, from his estranged uncle. And so he's thrilled when his uncle announces that he is ready to sell but with one major caveat--Penvale must marry his uncle's ward, Jane Spencer. When the two meet in London, neither is terribly impressed. Penvale finds Jane headstrong and sharp-tongued. Jane finds him cold and aloof. Nevertheless, they agree to a marriage in name only and return to the estate. There, Jane enlists her housekeeper for a scheme: to stage a haunting so that Penvale will return to London, leaving her to do as she pleases at Trethwick Abbey. But Penvale is not as easily scared as his uncle and as their time together increases, Jane realizes that she might not mind her husband's company all that much. With her trademark 'arch sense of humor and a marvelously witty voice' (Entertainment Weekly), Martha Waters crafts another delightful romp for all historical romance fans"--